Barsati junlaat kya hain? - Asimof Isak (Ferozesons; Pakistan, 2008)
Barsati Junlaat Kya Hain? explains the phenomenon of seasonal rains and their impact on the environment, shedding light on the significance of monsoons in nature's cycle.